Interest Rate Volatility of the Federal Funds Rate: Response of the Bank Indonesia and its Impact on the Indonesian Economic Stability - Imam Mukhlis; Isnawati Hidayah; Nora Ria Retnasih (Journal of Central Banking Theory and Practice, 2020)
This research aims to analyse the response of the Bank Indonesia (BI rate) to the Indonesian economic stability. The data analysis is stationarity test, model stability test, lag determination, Structural Vector Autoregression (SVAR), Impulse Response Function (IRF), and Variance Decomposition (VD). The research data is obtained from the publication provided by the Federal Reserve Data (FRED), the Bank Indonesia, and the Central Bureau of Statistics. The data used is since the third quarter of 2005 to the first quarter of 2017. The research results showed that the variable of the federal funds rate (FFR) significantly influences the exchange rate and the Consumer Price Index (CPI), but it does not significantly affect the BI rate, the amount of the money supply (M2), and Gross Domestic Product (GDP). The result of the IRF test showed that the BI rate, the amount of money supply, exchange rate (IDR/USD), GDP, and CPI positively and negatively respond the FFR change. The result of VD test indicated that the variation of the BI rate, the currency exchange rate, and CPI are mostly caused by the FFR variation.
Keywords: C58; E58; 330; Federal Funds Rate; BI Rate; Money Supply; Exchange Rate; Structural Vector Autoregression